XAFS study of tridentate Schiff base Ni(II) complexes having distorted octahedral geometry. (October 2020) - Gaur, A.; Joshi, S.K.; Nair, N. Nitin; Shrivastava, B.D.; Patel, R.N.; Jha, S.N.; Bhattacharyya, D.
Abstract: Distortion in mononuclear Schiff base nickel (II) complexes having pyridine and related N-containing heterocyclic derivatives has been studied using X-ray absorption spectroscopy. Extended X-ray absorption fine structure (EXAFS) analysis has been used to confirm the octahedral nature of Ni center and obtain a simple cluster of atoms around this metal ion. Ab-initio X-ray absorption near edge structure (XANES) simulations have been performed using FEFF9 for almost similar coordination around nickel metal in these complexes. The study supports variation in the order of distorted octahedral nature of Ni complexes with O and N atoms around the metal ions, with respect to changing nature of ligand. Theoretical XANES spectra generated for clusters of atoms around the metal ion have been correlated to corresponding p-DOS and s-DOS of the metal. Highlights: Distorted octahedral Ni complexes have been studied using EXAFS as well as XANES. Simulated XANES spectra show different features depending on metal p- and s-DOS. s-DOS contribution to rising part of edge has been found to vary among complexes. Constant p-DOS over 0–10 eV give rise to weak and split while line in complex 1 .